Shrinking cities in Romania. Orase românesti în declin. Vol. 1: Research and analysis. O cercetare critica. - (:unkn) unknown (DOM Publ., 2019)
This book looks at Romania as a case study nearly thirty years after the collapse of the Council for Mutual Economic Assistance and the Warsaw Pact. In a very short time, political and economic conditions across Eastern Europe changed drastically, with affected countries being confronted with a capitalist market economy. The current globalization model succeeds in stimulating overall economic growth in most nations, but does so at the cost of social and spatial division. The very substantial and precise study provides a deep understanding of these issues by analyzing the shrinking cities phenomenon. And they even go one important step further, by daring to formulate and initiate constructive ways to address these issues and envisioning perspectives for these marginalized places.
Keywords: Stadtentwicklung; Schrumpfung; Demographischer Wandel; Stadtgröße; Wirtschaftsentwicklung; Strukturwandel; Arbeitsmigration; Entvölkerung; Sozialinfrastruktur; Öffentlicher Raum; Stadtbild; Sanierungsbedarf; Schrottimmobilie; Postsozialismus